2013
DOI: 10.1159/000346257
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Three-Year Outcome of Renal Transplantation from Optimal Donors versus Expanded Criteria Donors

Abstract: Background/Aims: The shortage in organ supply has required the use of expanded criteria donors (ECD) for kidney transplantation. Current pre-transplant evaluations of ECD organs are based on histological, clinical or mixed criteria. This monocentric study investigates the predictivity of Karpinski’s histological score on 3-year graft function in renal transplant. Ex-post classification using Nyberg’s score was carried out to assess the reliability of a purely clinical score and its applicability for organ allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In addition, the incidence of DGF and acute rejection at 1 year posttransplant were not inferior in ECD recipients. These results are in agreement with those of other studies 1415…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the incidence of DGF and acute rejection at 1 year posttransplant were not inferior in ECD recipients. These results are in agreement with those of other studies 1415…”
Section: Discussionsupporting
confidence: 94%
“…The prospect of transplanting both kidneys from a high-risk donor, DKT, is a successful approach for optimizing the donor kidney pool [36]. The selection of kidneys for transplantation (SKT or DKT) includes donor data like age, donor history, renal function, macroscopic aspect and histological findings in kidney biopsy [1,13,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have argued for decreased cold ischemia time, using perfusion pumps rather than simple cold storage, selective use of ECDs for recipients with low PRA, or refinement of predictors for graft failure through kidney biopsy [3339]. Some of these studies report promising results using combinations of all of these techniques [40]. More recently, there has been progress diagnosing acute rejection through use of ultrasound or urine metabolites, which may improve the longevity of the allograft [39, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, newer studies have suggested that kidney biopsy may be a more effective way of predicting graft longevity [45]. There has been an attempt to standardize the biopsy-reading process with specialized pathologists and scoring systems [40,4648]. These scoring systems may supplement the predictive power of the KDPI.…”
Section: Discussionmentioning
confidence: 99%